Flexible singularisation and orientation of small delicate and asymmetric cylindrical parts - Chua, Patrick Soon Keong. (2008)
A parametric study on the singularisation and orientation of didicate and powdery asymmetric cylindrical parts with the objective of producing a workable design concept for developing a suitable non-vibratory feeder.